2022
DOI: 10.1021/acs.jproteome.1c00977
|View full text |Cite
|
Sign up to set email alerts
|

1H qNMR-Based Metabolomics Discrimination of Covid-19 Severity

Abstract: The coronavirus disease 2019 (Covid-19), which caused respiratory problems in many patients worldwide, led to more than 5 million deaths by the end of 2021. Experienced symptoms vary from mild to severe illness. Understanding the infection severity to reach a better prognosis could be useful to the clinics, and one study area to fulfill one piece of this biological puzzle is metabolomics. The metabolite profile and/or levels being monitored can help predict phenotype properties. Therefore, this study evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 70 publications
5
21
0
Order By: Relevance
“…As reported by independent studies, we observed increased abundance of phenylalanine with SARS-CoV-2 infection ( 32 , 49 , 50 ). Although differences between categories of severity did not reach statistical significance, phenylalanine has been implicated as a biomarker of COVID-19 severity ( 51 53 ).…”
Section: Discussionmentioning
confidence: 88%
“…As reported by independent studies, we observed increased abundance of phenylalanine with SARS-CoV-2 infection ( 32 , 49 , 50 ). Although differences between categories of severity did not reach statistical significance, phenylalanine has been implicated as a biomarker of COVID-19 severity ( 51 53 ).…”
Section: Discussionmentioning
confidence: 88%
“…Several studies on mild/moderate and acute COVID-19 patients have implicated the important functions of lipoproteins in disease development [12; 33; 36; 44; 45; 46; 47]. In our study, the four cohort groups were partially separated by the PCA (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Of note, a previously launched in vitro diagnostics research (IVDr) NMR analytical platform demonstrated that for given samples this method can discover quantitative data on metabolite and lipoprotein levels in analysed solutions from either blood serum and plasma (Letertre et al, 2021). The IVDr nMR platform had been already successfully implemented for COVID-19 phenotyping [12; 22; 28; 29; 30; 31; 32; 33; 34; 35]. The samples were collected dated from June 2020 to February 2021 and correspond to the wildtype/alpha mutant of the virus based on epidemiological knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted ROC curve analyses to compare SeptiCyte RAPID to other single biomarkers, specifically CRP, D-dimer, lactate, monocytes, and CD16-positive monocytes, for discriminating (critical + severe) vs. (moderate + mild) cases. These biomarkers have all been used previously by clinicians and investigators to assess the severity of COVID-19 clinical trajectories [ 21 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%